A Muscarone-Binding Material in Electroplax and Its Relation to the Acetylcholine Receptor, II. Dialysis Assay - O'Brien, R. D. (1970)
An equilibrium dialysis technique, applied to lyophilized particulate fractions of Torpedo electroplax, gave data consistent with a single kind of macromolecular binding of muscarone, with binding constant, 7 × 10(-7) M and an amount of 1 nmole per gram original electroplax. The effects on muscarone binding of 38 drugs suggested that muscarone binding reflected acetylcholine receptor activity. Of 18 enzyme preparations, only trypsin, chymotrypsin, and phospholipase C reduced binding activity, suggesting that a phospholipoprotein was binding. Partial „solubilization” of the binding protein was achieved, but the „solubilized” activity did not migrate on electrophoresis. Additional evidence was provided that acetylcholinesterase was not responsible for this muscarone binding.